Randomized controlled trial of social interaction police training - McLean, Kyle (Criminology & public policy, 2020)
Research We conducted a randomized-controlled trial (RCT) of a social interaction training program to determine its effectiveness in improving attitudes and behaviors among police officers. Survey data and a series of difference-in-difference tests found that participating in the training program improved attitudes with treatment group officers placing higher priorities on procedurally fair communication during a hypothetical officer-citizen encounter. An interrupted time-series analysis of official use-of-force reports provided no evidence that the training program altered officer behavior. Policy Implications Policing scholars and reformers have increasingly called for improvements to police training that emphasize communication and de-escalation skills. Although many programs addressing these issues exist, evidence of their effectiveness has been scarce. Our findings provide evidence that such training may improve police officer attitudes but perhaps not behaviors.